The relation between preoperative radiological sarcopenia and postoperative recovery of physical activity in older surgical cancer patients; an explorative study - S. Hendriks; M.G. Huisman; L. Weerink; L.T. Jonker; B.C. van Munster; J.J. de Haan; G.H. de Bock; B.L. van Leeuwen (Elsevier, 2024)
To identify older surgical cancer patients at risk of decreased postoperative recovery of physical activity (PA), this study assesses whether preoperative radiological sarcopenia (RS) is associated with a decreased ability to return to baseline PA. RS was defined as decreased psoas muscle mass or -density by gender-specific cut-offs on CT-scans at level of vertebra L3. PA was assessed as steps/day measured with PA tracker and recovery of PA was defined as >90% of preoperative steps/day at 3 months postoperatively. Of 44 included patients aged 65 and over undergoing oncologic surgery, 18 patients (41%) showed RS. Seventeen patients (39%) returned to baseline PA, of which eight patients had RS (47%). RS was not associated with a return to baseline PA (OR: 1.38, 95%CI 0.39-4.92, p = 0.61). In this exploratory study, no association was found between preoperative RS and recovery of PA postoperatively.